Does Foreign Direct Investment Foster China’s Economic Growth? - Yuan, Minhua; Ab-Rahim, Rossazana; Husaini, Dzul Hadzwan (International Journal of Economics and Financial Issues, 2025)
China is a developing country that has attracted the most foreign direct investment (FDI), making full use of the technology spillover effect. This study investigates the impacts of FDI and technology spillover on China's economic growth, focusing on its direct and indirect effects. Based on neoclassical and endogenous growth theories, FDI and technology spillover are the key variables, with trade openness, government expenditure, and total population as control variables, and economic growth as the dependent variable. This study employs a panel dataset from 30 Chinese provinces spanning 2000-2022. Methodologically, the Cross-Section Dependence test and Augmented Mean Group (AMG) model are used. Findings of direct effects confirm that research and development (R&D) and government expenditure significantly drive economic growth, while FDI and trade openness are both insignificant and negatively correlated. Indirect effects highlight R&D's significant role in the relationship between FDI and economic growth. Furthermore, there is significant heterogeneity between Eastern, Central, and Western regions. The implications of these findings are: first, fostering R&D investment is critical to magnifying the benefits of FDI and enhancing economic growth. Second, institutional innovations can attract high-quality foreign investment. Finally, aligning a high level of trade openness with growth policies is important.